New Choices, New Families How Lesbians Decide about Motherhood - Mezey, Nancy J. (Johns Hopkins University Press, 2008)
How do lesbians decide to become mothers or remain childfree? Why do new families form at particular historical moments? These questions are at the heart of Nancy J. Mezey's New Choices, New Families. Researchers, politicians, and society at large continue to debate the changing American family, especially nontraditional families that emerge from divorce, remarriage, grandparents-as-parents, and adoption. This ongoing discussion also engages the controversy surrounding the parental rights of same-sex couples and their families. New Choices, New Families enters into this conversation. Mezey asks why lesbians are forming families at this particular historical moment and wonders how race, class, sexual identity, and family history factor into the decision-making process. Drawing heavily from personal interviews, Mezey's groundbreaking analysis gives voice to groups long underrepresented in similar studies-black, Latina, working class, and childfree lesbians. Some chapters examine how childhood experiences contribute to the desire to become a mother, while others consider the influence of women's partners and careers. New Choices, New Families provides thoughtful insights into questions about sexual identity, social and cultural expectations, and what and who constitute a family.